Efficacy of cognitive bias modification interventions in anxiety and depressive disorders: a systematic review and network meta-analysis. (June 2020) - Fodor, Liviu A; Georgescu, Raluca; Cuijpers, Pim; Szamoskozi, Ştefan; David, Daniel; Furukawa, Toshiaki A; Cristea, Ioana A
Summary: Background: Cognitive bias modification (CBM) therapies, including attention bias modification, interpretation bias modification, or approach and avoidance training, are prototypical examples of mechanistically derived treatments, but their effectiveness is contentious. We aimed to assess the relative effectiveness of various CBM interventions for anxious and depressive symptomatology. Methods: For this systematic review and network meta-analysis, we searched PubMed, PsycINFO, Embase, and Cochrane Central Register from database inception up until Feb 7, 2020. We included randomised controlled trials of CBM versus control conditions or other forms of CBM for adults aged 18 years and older with clinical or subclinical anxiety or depression measured with a diagnostic interview or a validated clinical scale. We excluded studies comparing CBM with a non-CBM active intervention. Two researchers independently selected studies and evaluated risk of bias with the Cochrane Collaboration tool. Primary outcomes encompassed anxiety and depressive symptoms measured with validated clinical scales. We computed standardised mean differences (SMDs) with a restricted maximum likelihood random effects model. This study is registered with PROSPERO, CRD42018086113. Findings: From 2125 records we selected 85 trials, 65 (n=3897) on anxiety and 20 (n=1116) on depression. In a well connected network of anxiety trials, interpretation bias modification outperformed waitlist (SMD −0·55, 95% CI −0·91 to −0·19) and sham training (SMD −0·30, −0·50 to −0·10) for the primary outcome. Attention bias modification showed benefits only in post-hoc sensitivity analyses excluding post-traumatic stress disorder trials. Prediction intervals for all findings were large, including an SMD of 0. Networks of depression trials displayed evidence of inconsistency. Only four randomised controlled trials had low risk of bias on all six domains assessed. Interpretation: CBM interventions showed consistent but small benefits; however heterogeneity and risk of bias undermine the reliability of these findings. Larger, definitive trials for interpretation bias modification for anxiety might be warranted, but insufficient evidence precludes conclusions for depression. Funding: Romanian Ministry of Research and Innovation, The National Council for Scientific Research—The Executive Agency for Higher Education, Research, Development and Innovation Funding.